1998
DOI: 10.1074/jbc.273.22.13437
|View full text |Cite
|
Sign up to set email alerts
|

Negative Feedback Control of the Retinoid-Retinoic Acid/Retinoid X Receptor Pathway by the Human TR4 Orphan Receptor, a Member of the Steroid Receptor Superfamily

Abstract: Amino acid sequence analysis indicates that the human TR4 orphan receptor (TR4) is a member of the estrogen/thyroid receptor subfamily of the steroid/thyroid receptor superfamily and recognizes the AGGTCA direct repeat (DR) of the hormone response element. Here we demonstrate using the electrophoretic mobility shift assay that TR4 binds specifically to DR with a spacing of 1 and 5 base pairs (DR1 and DR5), which are the response elements for retinoic acid receptor (RAR) and retinoid X receptor (RXR), respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
64
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 30 publications
2
64
0
Order By: Relevance
“…In vitro data suggest that TR4 functions as a master regulator to modulate many signaling pathways, including induction of the ciliary neurotrophic factor alpha [5, 6], interfering with retinoic acid receptor/retinoid X receptor [7], thyroid receptor [8], androgen receptor [9], and estrogen receptor-mediated pathways [10], and facilitating viral infection and propagation of HPV-16 and SV40 [11]. Mice lacking Tr4 ( TR4KO ) have high rates of early postnatal mortality, show significant growth retardation [12], display reproductive defects in both genders [12, 13], abnormalities in spermatogenesis [14], reduced lipoprotein metabolism [15, 16], and reduced gluconeogenesis [17], as well as defects in cerebella development [18].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro data suggest that TR4 functions as a master regulator to modulate many signaling pathways, including induction of the ciliary neurotrophic factor alpha [5, 6], interfering with retinoic acid receptor/retinoid X receptor [7], thyroid receptor [8], androgen receptor [9], and estrogen receptor-mediated pathways [10], and facilitating viral infection and propagation of HPV-16 and SV40 [11]. Mice lacking Tr4 ( TR4KO ) have high rates of early postnatal mortality, show significant growth retardation [12], display reproductive defects in both genders [12, 13], abnormalities in spermatogenesis [14], reduced lipoprotein metabolism [15, 16], and reduced gluconeogenesis [17], as well as defects in cerebella development [18].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous data also showed that the TR4 has a better affinity than RXR␣ to recognize the DR1-HRE in the promoter of the cellular retinol-binding protein II gene (21). To examine whether TR4 can bind to the potential DR1-HRE (named TR4RE-HBV, nucleotide coordinates 1751-1778 of the HBV ayw DNA sequence) on the HBV core promoter (13), the electrophoretic mobility shift assay (EMSA) was performed with in vitro translated TR4 protein, using radiolabeled TR4RE-HBV oligonucleotides as probes.…”
Section: Tr4 Protein Binds Specifically To the Tr4re-hbv Consensus Simentioning
confidence: 99%
“…These findings suggest that these nuclear receptors in the liver can coordinately regulate gene expression by interacting with HRE sequences in the promoters of their target genes. Our data show that TR4 can interfere with a number of other nuclear receptors by competing for binding to the same HREs (21,22).…”
mentioning
confidence: 96%
See 2 more Smart Citations